Predicting the rate of adjuvant postoperative chemo/radiation in cervical cancer with tumor size ≥2 cm and <4 cm: An Israeli Gynecologic Oncology Group study. (June 2022) - Gemer, Ofer; Namazov, Ahmet; Ben-Arie, Alon; Eitan, Ram; Rabinovich, Alexander; Vaknin, Zvi; Armon, Shunit; Bruchim, Ilan; Levy, Tally; Ben Shachar, Inbar; Lavie, Ofer
Abstract: Objective: Women with cervical cancer who undergo radical hysterectomy are often treated postoperatively with chemoradiation. Patient selection that minimizes adjuvant treatment is valuable. We compared two methods for predicting postoperative adjuvant treatment of women with tumor size ≥2 cm and <4 cm. Study design: This multicenter retrospective study included 272 women with tumor size ≥2 cm and <4 cm. A receiver operating characteristic curve (ROC) analysis was used to determine the optimal tumor cutoff size to predict adjuvant treatment. A second analysis compared the rate of adjuvant treatment between women with and without lymph vascular space involvement (LVSI). Results: According to the ROC, the optimal cutoff value of tumor size for predicting adjuvant treatment was 2.95 cm (sensitivity 0.70, specificity 0.67). Tumors were ≥3.0 cm in 166 (61.0%) women. The rate of adjuvant treatment was higher in women with larger tumor diameter (73.8% vs. 47.9%, p < 0.0001). Of the 241 women with a LVSI record, LVSI was present in 81 (34%) women. Among women with LVSI, rates were higher of positive lymph nodes (41.0% vs 14.5%, p < 0.0001) and postoperative adjuvant treatment (83.3% vs. 53.7%, p < 0.001). Among women with tumor size ≥3.0 cm and LVSI, the rate of adjuvant treatment was 90.0%. In the multivariate analysis, both tumor size ≥3.0 cm and the presence of LVSI were independently associated with adjuvant treatment (OR 3.9, 95% CI 2.1–7.1; p < 0.0001 and OR 4.9, 95% CI 2.4–10.0; p < 0.0001, respectively). Conclusion: In women with cervical cancer who underwent radical hysterectomy, tumors ≥3 cm were associated with a >70% rate of adjuvant treatment, and LVSI was associated with a >80% rate. These data should be weighed in multidisciplinary consultation with radiation oncologists when deciding treatment strategy. Highlights: Selecting primary treatment of stage IB2 cervical cancer. Adjuvant chemo/radiation is higher in tumors larger than 3 cm and presence of LVSI. Multidisciplinary consultation with radiation oncologists could be considered.